Heterotetramerization of Plant PIP1 and PIP2 Aquaporins Is an Evolutionary Ancient Feature to Guide PIP1 Plasma Membrane Localization and Function - Bienert, Manuela D.; Diehn, Till A.; Richet, Nicolas; Chaumont, François; Bienert, Gerd P. (Frontiers in Plant Science, 2018)
Aquaporins are tetrameric channel proteins regulating the transmembrane flux of small uncharged solutes and in particular water in living organisms. In plants, members of the Plasma membrane Intrinsic Protein (PIP) aquaporin subfamily are important for the maintenance of the plant water status through the control of cell and tissue hydraulics. The PIP subfamily is subdivided into two groups, PIP1 and PIP2 that exhibit different water-channel activities when expressed in Xenopus oocytes or yeast cells. Most PIP1 and PIP2 isoforms physically interact and assemble in heterotetramers to modulate their subcellular localization and channel activity when they are co-expressed in oocytes, yeasts and plants. Whether the interaction between different PIPs is stochastic or controlled by cell regulatory processes is still unknown. Here, we analyzed the water transport activity and the subcellular localization behavior of the complete PIP subfamily (SmPIP1;1, SmPIP2;1 and SmPIP2;2) of the lycophyte Selaginella moellendorffii upon (co-)expression in yeast and Xenopus oocytes. As observed for most of the PIP1 and PIP2 isoforms in other species, SmPIP1;1 was retained in the ER while SmPIP2;1 was found in the plasma membrane but, upon co-expression, both isoforms were found in the plasma membrane, leading to a synergistic effect on the water membrane permeability. SmPIP2;2 behaves as a PIP1, being retained in the endoplasmic reticulum when expressed alone in oocytes or in yeasts. Interestingly, in contrast to the oocyte system, in yeasts no synergistic effect on the membrane permeability was observed upon SmPIP1;1/SmPIP2;1 co-expression. We also demonstrated that SmPIP2;1 is permeable to water and the signaling molecule hydrogen peroxide. Moreover, growth- and complementation assays in the yeast system showed that heteromerization in all possible SmPIP combinations did not modify the substrate specificity of the channels. These results suggest that the characteristics known for angiosperm PIP1 and PIP2 isoforms in terms of their water transport activity, trafficking and interaction emerged already as early as in non-seed vascular plants. The existence and conservation of these characteristics may argue for the fact that PIP2s are indeed involved in the delivery of PIP1s to the plasma membrane and that the formation of functional heterotetramers is of biological relevance.